2010
DOI: 10.1080/03602551003749536
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclay Modified Water-Blown Polyurethane Foams Derived from Bifunctional Soybean Oil-Based Polyol

Abstract: In this brief communication, we report on the modification of polyurethane (PU) foams based on bifunctional soy bean oil-based polyol by nanoclay. Presence of clay at small loading has been observed to make the foam system more rigid. Modification has been analyzed by measurements on density and compressive strength. In addition, differential scanning calorimetry and thermogravimetric analysis have been used to explain changes in properties of the foams. Scanning electron microscopy have been used to verify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…In fact, the main focus of the two investigations [14,15] is on the mechanical strength of PU-PCM foams. It can be concluded that no matter which catalyst is used, the cell size decreases in an appropriate ratio to the microcapsule contents due to the nucleation effect of adding fillers [27][28][29]. The mechanical strength can be improved with the nucleation effect, nevertheless this improvement cannot compensate for the negative influence induced by cell ruptures and particle aggregations.…”
Section: Pu Foams Containing Microencapsulated Pcmsmentioning
confidence: 99%
“…In fact, the main focus of the two investigations [14,15] is on the mechanical strength of PU-PCM foams. It can be concluded that no matter which catalyst is used, the cell size decreases in an appropriate ratio to the microcapsule contents due to the nucleation effect of adding fillers [27][28][29]. The mechanical strength can be improved with the nucleation effect, nevertheless this improvement cannot compensate for the negative influence induced by cell ruptures and particle aggregations.…”
Section: Pu Foams Containing Microencapsulated Pcmsmentioning
confidence: 99%
“…PU is a highly cross-linked polymer with an essentially closed-cell structure. Its low density, high strength-to-weight ratio and low thermal conductivity have made PU a dominant synthetic material on a global basis [2,3]. However, PU is flammable material without any additives, which easily results in fire hazard.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of nanolayered silica is one way to eliminate such disadvantages and modify polymer properties. Researchers showed that the use of a small amount of modified nanoclays and production of polyurethane-clay nanocomposite causes enhancement in mechanical and thermal properties, gas barriers and some other properties of such polymers remarkably [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The preparation of polyurethane-clay nanocomposites via in situ polymerization method has been the issue of many researches in past years [25,26,30,[40][41][42][43] .…”
Section: Introductionmentioning
confidence: 99%